The Board of Management : a study of operational effectiveness of the Boards of Management as vehicles for the participation of trustees, teachers, and parents in a sample of voluntary secondary and community schools in Ireland - Mungovan, James (Trinity College (Dublin, Ireland). School of Education, 2000)
Boards of management are part of an approach aimed at democratismg local school management through the involvement of parents and teachers with the school trustees in the local educational decision-making process. Board management implies the existence of processes that are democratic, and relationships that are collaborative and inclusive. The primary focus in this study was the perceptions of the board members as nominees of the primary stakeholders, and the school principals, on the effectiveness of their boards as instruments of participatory management. The study addressed the literature on school management to determine the critical issues for effective board management from two perspectives. It sought to determine what constituted effective management from the perspective of governments and proponents of local school based management - what was its rationale? It addressed the practice of school boards as it emerged from a range of studies - how far were the objectives being realised? The literature provided a basis for a conceptual synthesis, as well as themes and issues around board governance. These were addressed m the empirical study. The study addressed the following issues - the level of understanding of its role by the board and board members, the ability of the board to provide leadership through the development of policy for the school, its operating style understood in terms of nominee or delegate orientations, the responsiveness of the board to its constituencies, board accountability, the participatory processes of the board especially in relation to decision-making, its access to information, the professional/lay relationship on the board, training and on-going support for board members. The empirical study addressed the experience of practitioners serving as board members and principals on twenty-one voluntary secondary' boards and nineteen community boards drawn from voluntary secondary and community schools in Ireland.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin